INTEGRASI PENDIDIKAN KARAKTER, REVOLUSI MENTAL DAN NILAI-NILAI BUDAYA BIMA - Suparjan, Edy; Nurnaningsih, Nurnaningsih (Estoria: Journal of Social Science and Humanities, 2020)
This study aims to see, analyze and understand or understand the relationship between Character Education, Mental Revolution and Bima Cultural Values.And how it is implemented in school. This research uses descriptive methodwith document study approach. In its implementation in the field of CharacterEducation, it cannot be separated from the central role as the main campus ofstudents. In the family environment, students cultivate social behavior thatapplies in society, in the family environment, students are also formed mentally,emotionally and their character. Integration of Character Education, MentalRevolution and Bima cultural values must be applied at every level of educationstarting from elementary, junior high, high school to tertiary levels.Keywords: character education, mental revolution. cultural values